User modeling, adaptation, and personalization : 21th International Conference, UMAP 2013, Rome, Italy, June 10-14, 2013 Proceedings - Weibelzahl, Stephan; Micarelli, Alessandro; Semeraro, Giovanni (Lecture Notes in Computer Science, 2013)
This book constitutes the thoroughly refereed proceedings of the 21st International Conference on User Modeling, Adaption, and Personalization, held in Rome, Italy, in June 2013. The 21 long and 7 short papers of the research paper track were carefully reviewed and selected from numerous submissions. The papers cover the following topics: recommender systems, student modeling, social media and teams, human cognition, personality, privacy, web curation and user profiles, travel and mobile applications, and systems for elderly and disabled individuals.